Premarital Sex Behaviors Among College Youths of Kathmandu, Nepal - BC, GB; Basel, PL (Kathmandu University Medical Journal, 2014)
Backgroud Unhealthy premarital sex behavior leads to several health problems namely; sexually transmitted diseases (STDs), Human Immune Virus and Acquired Immune Deficiency Syndrome (HIV/AIDS), unwanted pregnancies, abortions and maternal deaths. Unwanted pregnancies and unsafe abortions are rampant in Nepal despite introduction of legal provision for safe abortion since 2003. Lately, unsafe sex and sex without condoms and drinking before sex is increasing in trend in youth population. The primary aim of this study was to explore the factors associated with premarital sex behaviors. Objectives The main objective of the study was to identify the premarital sex behaviors and related factors among college youths in Kathmandu, Nepal. Methods Descriptive and explorative study of size 230 college youths aged between 18- 24 years. Data were collected by self-administered questionnaire from February 26 to March 15, 2012. The reliability of the questionnaire was ensured by using Cronbach’s alpha. Results Late youths of age 20-24 were more likely to experience premarital sex than early youths of age 18-19 years old. Urban youths were less involved in premarital sex behavior than rural youth. Youths having negative attitudes towards premarital sex were more likely to experience premarital sex than a positive attitude. Youths who had good relationship with their parents had less premarital sex experience than youths having poor relationship with their parents. Conclusion One fifth of college youth had premarital sex experience where alcohol drinker had higher premarital sex experience than non-drinker. Youths having good peer norms were significantly less likely to experience premarital sex behaviors than youths having poor peer norms. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11019 Kathmandu University Medical Journal Vol.11(1) 2013: 27-31